2022
DOI: 10.1007/s11845-022-02936-9
|View full text |Cite
|
Sign up to set email alerts
|

Social media medical misinformation: impact on mental health and vaccination decision among university students

Abstract: Background The COVID-19 pandemic highlighted the need of social media as a medium for gathering health-related information. Simultaneously, a slew of false information, primarily about COVID-19's origin, dissemination, prevention, treatment, and fatality surfaced, making it difficult to distinguish fake from genuine material. However, the possible effects on mental health and the extent to which this influences our decisions, particularly regarding vaccination, are unknown. Aim The purpose of this questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 36 publications
0
14
1
Order By: Relevance
“…Information resources about COVID-19 vaccines are many, including scientific articles, internet pages, friends, and traditional media. Although a similar study in the Middle East found that social media had a different effect on the behavior of the population toward the virus or the vaccine [15], our study showed that people who took their vaccine knowledge from scientific evidence were the most willing to take the vaccine. It was reported that reading a scientific article about the available vaccines resulted in a significant increase in the willingness to take the vaccine [12].…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Information resources about COVID-19 vaccines are many, including scientific articles, internet pages, friends, and traditional media. Although a similar study in the Middle East found that social media had a different effect on the behavior of the population toward the virus or the vaccine [15], our study showed that people who took their vaccine knowledge from scientific evidence were the most willing to take the vaccine. It was reported that reading a scientific article about the available vaccines resulted in a significant increase in the willingness to take the vaccine [12].…”
Section: Discussioncontrasting
confidence: 69%
“…Previous studies showed that various factors play a role in vaccine hesitancy, including medical personnel, social media, lack of trust, and, most importantly, vaccine safety [12][13][14][15]. Based on a study done in France before vaccine emergence, 25% of people who refused to take the vaccine had concerns about its safety due to its fast development [16].…”
Section: Introductionmentioning
confidence: 99%
“…Among them is AstraZeneca, with an effectiveness of 76% [ 5 ], Sinopharm, with an effectiveness of 79% [ 6 ], and Sputnik V vaccine, with an effectiveness of 80% [ 7 ]. Despite the presence of some negative attitudes toward vaccination, these vaccines were widely spread [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study also showed that the experience of participants with people having COVID-19 had statistically significant association with undertaking more preventing behaviors. This can be viewed in the context of the provision of healthcare since it has been found that people who are involved in health-related professions have an increased intention to get vaccinated against COVID-19 as they have a high level of knowledge about this field, and they are aware of the severity of vaccination to improve the pandemic [ 30 ].…”
Section: Discussionmentioning
confidence: 99%